SUSTAINABLE DEVELOPMENT OF ENTREPRENEURSHIP IN AGRICULTURAL MANAGEMENT AND FOREIGN EXPERIENCES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article describes the achievements and disadvantages in the process of managing the agricultural sector based on innovative technologies and foreign experience in this area.